Mobilt Elektroencefalografi - Croft, John; Olsson, Christoffer (My University, 2019)
Today's technology is constantly undergoing new innovations and evolutions. In keeping with this trend, this project aims to take the well-established measuring technique of electroencephalography (EEG) and create a mobile implementation. The project has been performed at Chalmers. An Electroencephalography (EEG) is used to detect and measure ion currents in the brains nerve cells. These can be measured by attaching voltage sensitive electrodes on the scalp, and is used to determine di erence conditions in the brain, such as epilepsy, coma and brain death. The idea behind the project is that its mobility and availability can open an opportunity for large amounts of data. This large data set can potentially be used to analyse how humans catalogue what she learns, and how varying external stimuli a ects this process. Basic requirements include that it should function as a normal EEG, as well as there should exist a simple way to interact with the software. The project has consequently developed hardware to collect EEG-data, as well as created a GUI for easy use of the system. The project development is unfortunately an un nished product, and some of the initial goals have not yet been completed. The results of the project has resulted in a more in-depth knowledge of what an EEG is, and also the limitations that exists in programming languages and hardware when one tries to create a real time system. The results have been used as a knowledge base for another project, and aims to be used for more like-minded projects in the future.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology